Service-learning in higher education relevant to the promotion of physical activity, healthful eating, and prevention of obesity - Rosenkranz, Richard R. (My University, 2012)
Service-learning is a type of experiential teaching and learning strategy combining classroom instruction and meaningful community service and guided activities for reflection. This educational approach has been used frequently in higher education settings, including an array of disciplines such as medicine, theology, public health, physical education, nutrition, psychology, anthropology, and sociology. The purpose of the present review paper was to provide guidance on the use of service-learning within higher education, relevant to the preventive medicine and public health topics of healthful eating, physical activity, and obesity prevention. In service-learning, coursework is structured to address community needs, and to benefit students through the real-world application of knowledge. The benefits for students include positive impacts on social skills, empathy, awareness, understanding, and concern regarding community issues, plus greater confidence and skills to work with diverse populations, increased awareness of community resources, improved motivation, and enhanced knowledge. Educational institutions may also benefit through improved “town and gown” relations, as strong ties, partnerships, and mutually beneficial activities take place. The present literature review describes several service-learning applications such as nutrition education for kids, dietary improvement for seniors, foodservice recipe modification on a college campus, an intergenerational physical activity program for nursing home residents, motor skill development in kindergarteners, organized elementary school recess physical activities, health education, and obesity prevention in children. From this review, service-learning appears to have great potential as a flexible component of academic coursework in the areas of preventive medicine and public health.
Keywords: Service-learning; Higher education; Preventive medicine; Public health; Healthful eating; Physical activity; Obesity prevention; Health education; Community; Health; Learning; Teaching